Nursing care for colorectal cancer patients (Research, Society and Development, 2021)
This study discusses nursing care for patients with colorectal cancer. It aims to highlight nursing care for patients with colorectal cancer. For this, the following guiding question was used: What is the main nursing care necessary for patients with colorectal cancer? As inclusion criteria, scientific articles between the years 2016 to 2020 were used, in the databases, LILACS, BVS, SCIELO and PUBMED, in English, French and Spanish. As exclusion criteria, articles outside the research time frame and that did not address the theme were excluded. The results obtained through the 20 selected scientific articles brought about the elaboration of three thematic categories: The main nursing care for patients with colorectal cancer; Quality of life of ostomized patients with colorectal cancer; The importance of health education in patients with colorectal cancer. In conclusion, the importance of the nurse as a health educator and the Systematization of Nursing Care in monitoring the patient with colorectal cancer from diagnosis to hospital discharge was highlighted. It was also highlighted the importance of creating support networks for people affected with this disease and how health professionals need to be trained and updated to meet the needs of these patients in all areas of their lives.